Functional Requirements Elicitation in IoT Systems: a follow-up study - Paldês, Roberto Avila; Canedo, Edna Dias; Guimarães, Fernando de Albuquerque; Calazans, Angélica Toffano Seidel (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
As the Internet of Things (IoT) advances, specific views have been proposed for the entire software development cycle and also for Requirements Engineering (RE). The analysis of the use of RE techniques, tools, and models can contribute to obtain better results in this field. This paper presents a Systematic Mapping Study (SMS) to investigate techniques for Functional Requirements (FR) elicitation in IoT software systems, as well as gaps and limitations of current solutions. During the SMS, seventeen articles focused on FR in the IoT were found. The analysis was complemented with an input from the experience of practitioners who have dedicated to this topic, obtained through structured and semi-structured interviews. The results show that FR elicitation has started from the use of traditional techniques, but that these do not fully meet the specificities of the IoT. The majority of the models found are based on UML (Unified Modeling Language) and the most important techniques are based on scenarios. The tools that support these proposals are maturing or under development. In the conclusion, the study shows the advancements already achieved, as well as the challenges and opportunities that are still present.